Representasi Gerobak Sepeda Sebagai Alat Pengangkut Barang Bekas - ali ramadhan (Narada : Jurnal Desain dan Seni, 2018)
Bicycle cart as one of the tools used to help humans do their work. A carrier is a tool used to move objects to the desired place. By using a bicycle cart, humans can carry heavy loads from one place to another. Used goods are goods that are considered has been exhausted because it can not be used anymore so it will tend to be discarded by the owner.By using descriptive qualitative research method, this research is expected to represent bicycle cart as one of the tools used to transport used goods that can help scavengers in doing their work.In the eyes of scavengers, used goods still have value. So taken for re-sale. A scavenger uses a bicycle cart to be able to transport used goods in order to be resold but with a certain period until the cart is considered to be quite a lot of transport. So it takes time to collect used goods. So the bike cart can switch function as a second home for scavengers.